2000
DOI: 10.1046/j.1365-3059.2000.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crop and weed hosts of Ralstonia solanacearum biovar 2 in the hills of Nepal

Abstract: Common agricultural weeds and crops that grow in the high hills of Nepal were examined after artificial inoculation and under natural conditions in the UK and Nepal to determine whether such plant species could act as hosts to biovar 2 of Ralstonia solanacearum. Bacterial populations in the roots were determined 1 and 2 months after inoculation, and at various intervals after harvesting infected potato crops under natural conditions. Inoculated roots of the summer weeds Drymaria cordata and Polygonum capitata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 19 publications
0
26
0
2
Order By: Relevance
“…He added that five races have been identified within the species. Strains of R. solanacearum have also been divided into five host-specific races by Pradhanang et al (2000). However, the results of this study primarily indicated that bacterial wilt pathogen of potato; R. solanacearum is belonging to race 3 although no wilt symptom was observed in tomato.…”
Section: Identification Of Racesmentioning
confidence: 84%
“…He added that five races have been identified within the species. Strains of R. solanacearum have also been divided into five host-specific races by Pradhanang et al (2000). However, the results of this study primarily indicated that bacterial wilt pathogen of potato; R. solanacearum is belonging to race 3 although no wilt symptom was observed in tomato.…”
Section: Identification Of Racesmentioning
confidence: 84%
“…He added that five races have been identified within the species. Strains of R. solanacearum have also been divided into five host-specific races by Pradhanang et al [46]. The dendrogram based on Nei's [34] genetic distance using the Unweighted Pair Group Method of Arithmetic Means (UPGMA) indicated the segregation of 28 isolates of R. solanacearum grouped into seven, which were clustered into two major clusters: cluster 1 and cluster 2.…”
Section: Isolatesmentioning
confidence: 99%
“…It mainly attacks potato, tomato (especially when planted after infected potato), geranium, occasionally Pelargonium zonale, eggplants, capsicum, and some solanaceous weeds like Solanum nigrum and Solanum dulcamara (Martin & French, 1985;Janse, 1991;French, 1994). Race 3 also infects a number of non-solanaceous weeds asymptomatically (Wenneker et al, 1999;Pradhanang et al, 2000). This race has a long association with potatoes and has an optimum temperature of 27 -28°C (French, 1994).…”
Section: The Pathogenmentioning
confidence: 99%